Potencialidades alelopáticas e identificação de algumas substâncias de folhas de Eupatorium maximiliani Schrad - Corrêa, Josirley de Fátima (1996)
In this work, was studied the allelopatic potential of the extract of Eupatorium maximiliani Schrad. leaves, prepared exhaustively in chloroform: methanol 2:1 (CM) upon four cultivated species and two species considered as crop invasers. The CM extract decreased significantly the germination of lettuce (Lactuca sativa), amaranth (Amaranthus sp.) and picão preto (Bidens pilosa) seeds, being that for the two latter species, there was 100 % of inhibition had taken place. The growth of radicle of lettuce, bean (Phaseolus vulgaris L.) and rice (Oryza sativa) were also significantly reduced. To com (Zea mays L.), no significant effect occurred in any of the analyzed parameters. The CM extract was later fractioned in gel silica column, submitted to TLC (Comparative thin layer chromatography) for isolation, identification and verifícation of the allelopatic activities of substances present in the extract. A number of fractions resultant from this process showed activity in germination and/or growth of lettuce radicle, this is, several compounds were responsible for the activity of the Eupatorium maximiliani leaf extract. By means of H'MNR, C,¹³MNR, IV and EM, two flavonoids were identified: 5,6,7,3',4', 5'-Hexametoflavon and 5,6,7,3',4', 5'-Hexametoflavonan. Bioassays on Petri dish revealed that the former substance stimulated both germination and growth of radical of lettuce seedlings, although also to the latter parameter, the results have been significant. The ativity of the other flavonoid was not assayed individually however fraction 6 from which it was isolated showed significant biological activity. These results proved the allelopathic potential of the extract of Eupatorium maximiliani Schrad leaves and point out that various substances are responsible for their inhibitory action which, in an individual manner, can cause different effects.